Identifying Architectural Affiliation Forms of the Campus University of Blida 1,"Saâd Dahleb", (Arch. Walter Netsch; 1981–1989) - Youcef Chennaoui; Imen AKEBLERSANE (Environmental Science and Sustainable Development)
During the mid-20th century, Walter Andrew Netsch, an American architect, introduced a groundbreaking conceptual method called the Theory of Fields. This approach focused on networks and the manipulation of geometric frames. One of his several undertakings included the construction of the University of Blida in Algeria during the early 1980s. This article is focused mainly on a geometric analysis of the main sections of the building's structure. Its objective is to identify the numerous mathematical relationships, geometric transformations, and other components that regulate the project in its entirety. Therefore, it appears that the University of Blida includes several concepts outlined in the architect's innovative approach to architectural composition, which incorporates components of traditional architecture. Advanced geometric practice has shaped a mathematical structure that serves as the university's compass. The latter is derived from a scholarly collection of square combinations that use ratios of 1/2 and 1/5 and a geometrical framework based on the series of Fibonacci numbers.